PENGARUH PELAYANAN PERIZINAN ONLINE TERHADAP KEPUASAN MASYARAKAT DI KABUPATEN TAKALAR - Annisa, St Murda; Haerana, Haerana; Arfah, Sitti Rahmawati (Universitas Muhammadiyah Makassar, 2024)
This study aims to determine how much influence online licensing services have on community satisfaction at the Investment Service and One-Stop Integrated Services in Takalar Regency. This research is a quantitative type. Data collection techniques using questionnaires. The analysis technique uses simple linear regression analysis. The validity of the data is obtained through validity and reliability tests. The results of this study indicate that online licensing services have a positive and significant effect on community satisfaction. Based on the results of the summary model output, the regression value (R) is 0.839 and is positive and the R Square value is 0.704, it can be concluded that variable X (online licensing services) has an influence of 70.4% on variable Y (public satisfaction) and the rest of 29.6% influenced by other factors. Which means the online licensing service site at the Investment Service and One-Stop Integrated Service of Takalar Regency is quite good at increasing community satisfaction.